2022
DOI: 10.1186/s40814-022-01030-2
|View full text |Cite|
|
Sign up to set email alerts
|

Physiotherapy interventions encouraging frequent changes of the body position and physical activity for infants hospitalised with bronchiolitis: an internal feasibility study of a randomised control trial

Abstract: Background The effect of a treatment that includes frequent changes of the body position for infants with bronchiolitis has not been evaluated, although it is often used in Swedish hospitals. Because of this, a randomised control trial (RCT) has begun with the aim to evaluate this treatment, comparing the effect of an individualised physiotherapy intervention, a non-individualised intervention, and standard care in a control group. The objective of this internal pilot study was to address uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors reported an error in the heading “Primary outcome measure” found on page 4. The heading should be at the same level as “ The safety analysis ” further down and “ The recruitment ” and “ Retention ” on the page before under the heading Outcomes.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error in the heading “Primary outcome measure” found on page 4. The heading should be at the same level as “ The safety analysis ” further down and “ The recruitment ” and “ Retention ” on the page before under the heading Outcomes.…”
mentioning
confidence: 99%